ERCP and SARS-COV-2: an urgent procedure that should be immune. (2nd August 2020) - O'Grady, John; Leyden, Jan; MacMathuna, Padraic; Stewart, Stephen; Kelleher, T. Barry
Abstract: Background: Radical changes to clinical and endoscopy practice have been rapidly introduced following the spread of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Urgent endoscopies are, however, intended to proceed as normal with additional personal protective procedures. A perceived reduction in hospital attendances may suggest a number of urgently indicated endoscopic retrograde cholangio-pancreatographies (ERCPs) are being missed. Objectives and Methods: A review of all ERCPs carried out in a large tertiary referral endoscopy unit under healthcare restrictions was compared to the same time period in previous years. The intention was to determine if ERCPs are proceeding as normal or if there is a difference in referral characteristics. Results: Under service restrictions (13 March to the end of April 2020), 55 ERCPs were performed compared with 87 ERCPs in 2019. Similar numbers to 2019 were also recorded in the preceding years. One case of coronavirus disease 2019 (COVID-19) was reported in a patient in the days following ERCP, with no cases notified among staff related to endoscopy. Conclusions: A reduction in ERCP referrals raises concern that a cohort of patients with significant biliary disease remain undetected. Whether this results in later, and more severe, presentation remains to be seen but a potential surge in such cases could significantly burden all future endoscopy planning services.